HOME-BASED EARLY WRITING ACTIVITIES: THE PERSPECTIVE OF PARENTS IN A LATVIAN CONTEXT - Laganovska, Egija; Margeviča-Grinberga, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Students entering school with underdeveloped writing skills often face academic challenges. Addressing and improving these skills at the preschool level is a critical instructional goal. Early engagement in writing activities with parents and adults at home, beginning at a young age, is crucial in shaping children's writing identities and methods. While student motivation is vital in developing writing abilities, the role of parents in encouraging and nurturing these skills is equally important. This study aims to explore how parental involvement aids in developing early children's writing skills. Data were collected through surveys conducted with parents of 3-6-year-old preschoolers, focusing on their writing support and parenting practices. This research seeks to understand the role of parents in facilitating early writing activities at home. The study's primary objective is to examine parents' perspectives on enhancing their children's early writing skills within a home environment. Active participation by parents in their children's writing activities, including practices like reading together, encouraging daily writing, and providing constructive feedback, has shown positive outcomes. However, some parents reported challenges such as limited time or resources, affecting their ability to support their child's writing development effectively.